2016
DOI: 10.1016/j.urology.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Influence and Impact of Cognitive Trajectories on Outcome in Patients Undergoing Radical Cystectomy: An Observational Study

Abstract: Objectives: To evaluate cognitive trajectories after radical cystectomy and their impact on surgical outcomes, including urinary continence. Results: Mean age was 67.9 ± 9.3 years (range 40 -88 years). Sixty-six patients (73.3%) had stable cognition, nine patients (10.0%) persistent and seven patients (7.8%) transient deterioration, five patients (5.6%) persistent and three patients (3.3%) transient improvement. An impaired preoperative cognition was the only significant risk factor of short-term cognitive det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The majority of patients presented a postoperative stable MMSE outcome, although pre-existing deficits were found to be the greatest risk factor for postoperative deterioration. 23 Similarly, a study from 2013 already showed that preoperatively lower MMSE scores were associated with a higher probability of developing postoperative delirium and the need for surgical revision in patients undergoing RC, although no assumptions on MCI prevalence can be drawn from this trial. 24 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The majority of patients presented a postoperative stable MMSE outcome, although pre-existing deficits were found to be the greatest risk factor for postoperative deterioration. 23 Similarly, a study from 2013 already showed that preoperatively lower MMSE scores were associated with a higher probability of developing postoperative delirium and the need for surgical revision in patients undergoing RC, although no assumptions on MCI prevalence can be drawn from this trial. 24 …”
Section: Discussionmentioning
confidence: 98%
“…The majority of patients presented a postoperative stable MMSE outcome, although pre-existing deficits were found to be the greatest risk factor for postoperative deterioration. 23 Similarly, a study from 2013 already showed that preoperatively lower MMSE scores were associated with a higher probability of developing postoperative delirium and the need for surgical revision in patients undergoing RC, although no assumptions on MCI prevalence can be drawn from this trial. 24 Besides determining the prevalence of MCI in patients with MIBC before RC and identifying possible risk factors, the aims of this study included comparison of DemTect, MMST, and clock drawing test results as well as differentiation of MCI from anxiety and depression and to examine the relationship between MCI and perioperative complication rates.…”
Section: Discussionmentioning
confidence: 98%
“…Assessment of cognitive impairment (CI), frailty, dexterity, or factors related to patient preferences are recommended [ 9 ], however, correlation of these factors is usually evaluated with postoperative outcomes, not upon qualification for UD [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%